Determinants of Group Perpetrated Violence Based on Sexual Orientation - Hudepohl, Adam David (2009)
The purpose of this study was to examine group perpetrated antigay violence. Specifically, the effects of MGRS, peer dynamics, and increases in negative affect on antigay aggression were examined. The differential utility of aggression toward gay and heterosexual targets in relieving a state of negative affect (e.g., anger, fear) was also evaluated. Participants completed questionnaires that included a measure of MGRS, and then were assigned to one of three group conditions(individual, stranger, and friend). Participants then viewed a video depicting male-male intimacy and competed in the TAP against either a fictitious gay or heterosexual opponent. Results showed a main effect for condition, such that higher levels of aggression were observed in the group, relative to the individual, conditions. Analyses also revealed a significant positive relation between MGRS and aggression among participants competing with a stranger against a heterosexual opponent. Neither condition nor opponent differentially predicted changes in negative affect